Functional gastrointestinal and somatoform symptoms five months after SARS‐CoV‐2 infection: A controlled cohort study - Noviello, Daniele; Costantino, Andrea; Muscatello, Antonio; Bandera, Alessandra; Consonni, Dario; Vecchi, Maurizio; Basilisco, Guido (Neurogastroenterology and motility, 2022)
Background Gastrointestinal infections represent a risk factor for functional gastrointestinal and somatoform extraintestinal disorders. We investigated the prevalence and relative risk (RR) of gastrointestinal and somatoform symptoms 5 months after SARS‐CoV‐2 infection compared with a control cohort. Methods One hundred and sixty‐four SARS‐CoV‐2 infected patients and 183 controls responded to an online questionnaire about symptoms and signs during the acute phase of the infection and after 4.8 ± 0.3 months. Presence and severity of gastrointestinal symptoms, somatization, anxiety, and depression were recorded with standardized questionnaires. Stool form and presence of irritable bowel syndrome (IBS) were also recorded. Any association between exposure to infection and symptoms was evaluated by calculating crude and adjusted RR values and score differences with 95% confidence intervals (CI). Key Results Fever, dyspnea, loss of smell/taste/weight, diarrhea, myalgia, arthralgia, and asthenia were reported by more than 40% of patients during the acute phase. Compared with controls, adjusted RRs for loose stools, chronic fatigue, and somatization were increased after infection: 1.88 (95% CI 0.99–3.54), 2.24 (95% CI 1.48–3.37), and 3.62 (95% CI 1.01–6.23), respectively. Gastrointestinal sequelae were greater in patients with diarrhea during the acute phase. Conclusions & Inferences Mild gastroenterological symptoms persist 5 months after SARS‐CoV‐2 infection, in particular in patients reporting diarrhea in the acute phase. Infected patients are at increased risk of chronic fatigue and somatoform disorders, thus supporting the hypothesis that both functional gastrointestinal and somatoform disorders may have a common biological origin. Mild gastrointestinal symptoms persist 5 months after SARS‐CoV‐2 infection together with an increased risk of chronic fatigue and somatoform symptoms. These results support the hypothesis that both functional gastrointestinal and somatoform disorders may have a common biological origin.